PROTEIN SPARING EFFECTS OF CARBOHYDRATE IN THE PRACTICAL DIETS OF Oreochromis niloticus - ORIRE, A.M; SADIKU, S.O.E. (Nigerian Journal of Fisheries, 2011)
A feeding trial was conducted to establish protein sparing effects of various lipid sources in Oreochromis niloticus fingerlings mean weight 8.05 ± 0.05 g for eight weeks. Nine experimental diets and one commercial reference diet was used for the trial. The experimental diets consisted of three levels of carbohydrate (C) and protein (P) designated as 10C:30P, 30C:25P and 50C:20P ratios. Three carbohydrate sources used were cornfibre, cornstarch and glucose-D. The result obtained showed significant differences (P < 0.05) among the carbohydrate/protein ratios fed to O. niloticus. However, the cornstarch based diets spared protein at 30% inclusion level bringing down crude protein to 25%. While, glucose based diets could spared protein up to 50% inclusion level but had a decline in growth towards the end of the feeding trial. The cornfibre based diets least spared protein for growth. Keywords: , , , .